Advances in librarianship. Vol. 27 - Lynden, Frederick C. (Emerald, 2004)
Critically acclaimed since its inception, Advances in Librarianship continues to be the essential reference source for developments in the field of libraries and library science. Articles published in the serial have won national prizes, such as the Blackwell North America Scholarship Award for the outstanding 1994 monograph, article, or original paper in the field of acquisitions, collection, development, and related areas of resource development. All areas of public, college, university, primary and secondary schools, and special libraries are given up-to-date, critical analysis by experts engaged in the practice of librarianship, in teaching, and in research.
Includes index.
Keywords: Library science.; Information science.; elektronické knihy; electronic books